Accurate Detection of the Four Most Prevalent Carbapenemases in E. coli and K. pneumoniae by High-Resolution Mass Spectrometry - Foudraine, Dimard E.; Dekker, Lennard J. M.; Strepis, Nikolaos; Bexkens, Michiel L.; Klaassen, Corné H. W.; Luider, Theo M.; Goessens, Wil H. F. (Frontiers in Microbiology, 2019)
Background: At present, phenotypic growth inhibition techniques are used in routine diagnostic microbiology to determine antimicrobial resistance of bacteria. Molecular techniques such as PCR are often used for confirmation but are indirect as they detect particular resistance genes. A direct technique would be able to detect the proteins of the resistance mechanism itself. In the present study targeted high resolution mass spectrometry assay was developed for the simultaneous detection of KPC, OXA-48-like, NDM and VIM carbapenemases. Methods: Carbapenemase specific target peptides were defined by comparing available sequences in Genbank. Selected peptide sequences were validated using 62 Klebsiella pneumoniae and Escherichia coli isolates containing: 16 KPC, 21 OXA-48-like, 16 NDM, 13 VIM genes and 21 carbapenemase negative isolates. Results: For each carbapenemase, two candidate peptides were validated. Method validation was performed in a blinded manner for all 83 isolates. All carbapenemases were detected. The majority was detected by both target peptides. All target peptides were 100% specific in the tested isolates and no peptide carry-over was detected. Conclusion: The applied targeted bottom-up mass spectrometry technique is able to accurately detect the four most prevalent carbapenemases in a single analysis.